2014
DOI: 10.1016/j.archoralbio.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Is the side with the best masticatory performance selected for chewing?

Abstract: Highlights:There is a positive association between the preferred chewing side and the more efficient side Alternate unilateral chewers masticate more efficiently than consistent unilateral chewers.Alternate unilateral chewers can masticate as or more efficiently when they chew unilaterally.Page 2 of 20 Objective: This study assessed the degree of relationship between masticatory laterality and lateral asymmetry of masticatory performance using silicon pieces enclosed in a latex bag.Design: Forty-two young adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 26 publications
1
50
0
Order By: Relevance
“…It is well known that the majority of people chew more on one particular side, i.e., they have a masticatory laterality (Diernberger, Bernhardt, Schwahn, & Kordass, 2008;Martinez-Gomis et al, 2009; . Although bilateral chewers were observed to chew more efficiently than unilateral chewers (Farias Gomes, Custodio, Moura Jufer, Del Bel Cury, & Rodrigues Garcia, 2010;Rovira-Lastra et al, 2014), no direct relation has been demonstrated (Rovira-Lastra et al, 2014). Chewing rate, defined as the frequency of chewing cycles per unit of time, seems to be remarkably stable within individuals, even across different days and foods (White et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that the majority of people chew more on one particular side, i.e., they have a masticatory laterality (Diernberger, Bernhardt, Schwahn, & Kordass, 2008;Martinez-Gomis et al, 2009; . Although bilateral chewers were observed to chew more efficiently than unilateral chewers (Farias Gomes, Custodio, Moura Jufer, Del Bel Cury, & Rodrigues Garcia, 2010;Rovira-Lastra et al, 2014), no direct relation has been demonstrated (Rovira-Lastra et al, 2014). Chewing rate, defined as the frequency of chewing cycles per unit of time, seems to be remarkably stable within individuals, even across different days and foods (White et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A test medium known as "bagged silicone" was used for 20 cycles to comminute the pieces (Flores-Orozco, Rovira-Lastra, Willaert, Peraire, & Martinez-Gomis, 2016). Optosil tablets (5 mm thick, 20-mm diameter) were produced as described by Albert, Buschang, & Throckmorton (2003), and cut into quarters, and three quarters of a tablet was placed in a latex bag, which was sealed with cyanoacrylate adhesive (Rovira-Lastra et al, 2014). The masticatory assay was repeated four more times, and the particles from the five assays were collected to evaluate the masticatory performance.…”
Section: Masticatory Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Several functional or postural lateral preferences have been related to masticatory laterality, though peripheral factors seem to be more closely related to the PCS . The side with more occluding teeth, more severe occlusal wear, higher bite force and better masticatory performance is more frequently chosen for chewing . While two studies found that individuals with missing unilateral posterior teeth or with asymmetric shortened dental arches tended to chew more unilaterally than healthy dentate individuals, another study reported similar distributions of chewing side preference in patients missing teeth on the right side, on the left side and in both sides .…”
Section: Introductionmentioning
confidence: 99%
“…Masticatory laterality can be defined as a functional asymmetry appearing when one side is preferred over the other side for chewing and can be assessed quantitatively by an asymmetry index . Among the objective methods, the use of bagged silicone to assess either the first cycle or all cycles has shown a high level of reproducibility and validity . Furthermore, the use of a visual analogue scale (VAS) is a valid and reliable method for assessing the degree of subjective masticatory laterality …”
Section: Introductionmentioning
confidence: 99%